Expanding Financial Reporting and Auditing Knowledge in Latin America and the Caribbean : CReCER and the Community of Practice - Martínez, David (World Bank, Washington, DC, 2012)
The main objective of CReCER is to create greater awareness of the importance of sound financial reporting and auditing for the development of a well functioning market economy and of an efficient public sector, which in turn are the cornerstone for equitable and sustainable economic development, and to promote the adoption of international standards for corporate financial reporting and auditing. CReCER is relevant to the work and interests of policymakers, senior civil servants, financial sector regulators, standard-setters, academics, accountants and auditors, private sector stakeholders, and regional and international organizations, including the donor community. The Spanish Fund for Latin America and the Caribbean (SFLAC) has funded the creation of the CReCER Community of Practice (CoP) that brings these achievements together.